Factors Related to the Incidence of Type 2 Diabetes Mellitus at the North Toto Health Center - Moh. Thamrin Happy; Sirajuddien Bialangi; Nikmatisni Arsad (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Type 2 Diabetes Mellitus (DMT2) is a non-communicable disease that continues to experience an increase in cases and is a global and national health problem. Globally, the number of cases reached 537 million in 2023 and is expected to increase to 700 million by 2045. In Indonesia, 19.5 million cases were recorded in 2021. Meanwhile, in Gorontalo Province there are 10,735 patients in 2024, and in the North Toto Health Center there are 109 patients in 2025. The incidence of this disease is influenced by various risk factors, such as diet, physical activity, obesity, family history, and consumption of sugar-sweetened beverages (SSB). This study aims to analyze the relationship between these factors and the incidence of Type 2 Diabetes Mellitus. Quantitative research type, analytical survey method with cross-sectional design. The total sample of 81 respondents was selected using accidental sampling techniques. Data collection was carried out using FFQ, GPAQ, and questionnaires that were compiled and validated by the researcher. The data was analyzed using the chi-square test to find out the relationships between variables. The results showed that diet (p=0.010), physical activity (p=0.000), obesity (p=0.002), and SSB consumption (p=0.037) were associated with the incidence of Type 2 Diabetes Mellitus, while family history was not related (p=0.227). There is a relationship between diet, physical activity, obesity, and consumption of sugar-sweetened beverages (SSB) with the incidence of DMT2. On the other hand, the family history did not show a relationship with the incidence of DMT2 at the North Toto Health Center. It is recommended to the public to adopt a healthy diet, increase physical activity regularly, maintain an ideal weight, and limit the consumption of sweetened beverages to reduce the risk of DMT2.